Evaluasi Dan Redesign Website Menggunakan System Usability Scale Dan Automated Software Testing - Suryawan, I Gede Totok; Satyawati, I Gusti Agung Ayu Ari; Purnama, I Wayan Adi; Arsana, I Made Dwi Putra (Universitas Pendidikan Ganesha, 2022)
This paper discusses the evaluation and redesign of the STIKI Indonesia website from the usability aspect using the System Usability Scale and User Interface Design as well as the performance aspect using the Pingdom software. This evaluation and redesign is important to do considering that since this website is online, it has only been evaluated once, from the analysis conducted on 19 leaders, the Head of the Institute / UPT STIKI Indonesia that 63.2% said the old website did not contain the expected content, 57.9% stated that there was a plan to load content, 100% agreed that the website content needed to be remapped and the website needed to be redesigned. Furthermore, after the redesign, the new website was evaluated by 40 new STIKI Indonesia students consisting of 25 men and 15 women, with an age range of 17 to 20 years. The results of the System Usability Scale evaluation get an average score of 85.8 or grade A. The average result of the User Interface Design evaluation is 8.4. The results of the performance evaluation using Pingdom get a performance grade of 99 or A.